Perlindungan Hukum Terhadap Anak Perempuan Dalam Kasus Penelantaran - Diana Permata Hati; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Legal protection for abandoned girls in Indonesia faces several fundamental issues. Firstly, inconsistent law enforcement often leads to many abandonment cases not being addressed. Secondly, the socialization of children's rights remains insufficient, leaving society, including parents, unaware of their protective roles. Thirdly, low community awareness of abandonment issues exacerbates the situation. This study aims to analyze the effectiveness of existing legal policies and provide strategic recommendations for improving legal protection for girls. The methodology employed is a juridical-normative approach, involving an analysis of relevant legislation and interviews with legal practitioners and child protection organization members. The research findings indicate that enhancing cross-sector collaboration and better socialization of children's rights are essential for creating more effective legal protection for abandoned girls.